In vitro propagation oflemon balm (Melissa officinalis L.) through nodal bud culture of adult plant - KUKREJA, A K (Journal of Spices and Aromatic Crops, 1999)
A simple and efficient two step procedure for in vitro high frequency plant regeneration was developed for clonal propagation oflemon balm (Melissa officinalis) using nodal explants. Nitsch and Murashige and Skoog’s medium supplemented with a-naphthalene acetic acid (1.0 mgl-1) supported axillary shoot growth and induction of roots in cultured explants. Nitsch medium showed better morphogenetic response than Murashige and Skoog’s medium. Murashige and Skoog’s medium fortified .with 2 mgP of either 6,benzyl aminopurine or 6-methyl aminopurine induced rapid proliferation of shoots. Rooting of the differentiated shoots was readily achieved with auxins fortified to Nitsch medium. The plantlets exhibited 80-90% success in establishment under glasshouse conditions.